Interpreting the Psalms. An Exegetical Handbook, Mark D. Futato : book review - Weber, Beat (Old Testament essays, 2008)
The new series 'Handbooks for Old Testament Exegesis' (HOTE), edited by David Howard, has an evangelical commitment. It gives basic knowledge and methodological skills for exegesis of the main genres of Old Testament literature to students of theology. After the first volume, written by Robert B. Chisholm for the study of the 'Historical Books' (2006), this book on the Psalms is the second published in the series. Mark Futato, professor at 'Reformed Theological Seminary' in Orlando, USA, begins his volume with the statement: 'The book of Psalms is perhaps the most frequently used book of the Old Testament' (p. 17).